2009
DOI: 10.1007/s11605-008-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Replaced Right Hepatic Artery at the Time of Pancreaticoduodenectomy

Abstract: Herein we describe a technique to reconstruct a replaced right hepatic artery following resection of the vessel en bloc with the tumor during a pancreaticoduodenectomy, using inflow from the gastroduodenal artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 3 publications
(3 reference statements)
0
21
0
Order By: Relevance
“…However, in the context of a PD are not so clear. Although we have not identified any inadvertent section of the variants in our study, there are some case-series that reported compatible findings with hepatic necrosis or ischemia of the hepato-jejunal anastomosis (16)(17)(18). In the context of PD, the iatrogenic injury of a RHA may pose a risk that leads to a biliary fistula secondary to an ischemic hepato-jejunal anastomoses ischemia, despite the existence of a hiliar vascularization.…”
Section: Discussionmentioning
confidence: 54%
“…However, in the context of a PD are not so clear. Although we have not identified any inadvertent section of the variants in our study, there are some case-series that reported compatible findings with hepatic necrosis or ischemia of the hepato-jejunal anastomosis (16)(17)(18). In the context of PD, the iatrogenic injury of a RHA may pose a risk that leads to a biliary fistula secondary to an ischemic hepato-jejunal anastomoses ischemia, despite the existence of a hiliar vascularization.…”
Section: Discussionmentioning
confidence: 54%
“…Several reports have shown that RARHA resection and reconstruction are feasible and safe. 3,7 In fact, two patients in our series had reconstruction without specific morbidity. Numerous types of reconstruction are available to pancreatic surgeons whereas simple ligation was reserved for a patient with RARHA Michels type 6.…”
Section: Discussionmentioning
confidence: 73%
“…Safe ligation of small caliber accessory right hepatic artery (Michels type 6, 7, or 8) has been described as has reconstruction of replaced right hepatic artery (Michels type 3, 4). 3,7,8 The aim of this study was to determine postoperative course, quality of oncologic resection, and overall survival in patients with RARHA undergoing PD for PA.…”
mentioning
confidence: 99%
“…In the others patients, the concomitant presence of main right hepatic artery allow not to perform revascularization procedures. This technique also described by Allendorf et al [13] is interesting but requires the non-invasion of the gastroduodenal artery by the tumor. An alternative technique is the use of a saphenous vein interposition graft as bridging procedure.…”
Section: Discussionmentioning
confidence: 94%